(untitled) (Academicia Globe: Inderscience Research, 2023)
In this article, opinions are widely covered about the organization of Independent Education in connection with the abilities, talents, opportunities, potential, and interests of students in schools, the development of cognitive abilities of students, the study of aspects that should be paid attention to taking into account the activities of students to receive independent education, ways to develop the innovative activity of students